Book Review: Making Space for Indigenous Feminism - Charron, Nadine (Gender and Development, 2008)
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; critique de livre; féminisme autochtone; histoire et politique; militance; pol4105; pol5185; premier cycle; périodes historiques; régions géographiques; thématiques

L'association des femmes inuites du Nunavik Saturviit : porteuses d'espoir et de paix - Koperqualuk, Lisa Q. (2008)
La revue est disponible gratuitement à cette adresse: https://numerique.banq.qc.ca/patrimoine/details/52327/21235?docref=7WwAmupy7jFapVusT6o59A
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; environnement; famille; féminisme autochtone; inégalités; maternité; nunavik; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; violences

Anishnaabe-Kwe, traditional knowledge, and water protection - McGregor, Deborah (Canadian Woman Studies, 2008)
26CANADIAN WOMAN STUDIES/LES CAHIERS DE LA FEMMEDans cet article, l’auteure partage ses expériences de travail sur les questions environnementales, particulièrement sur celles qui concernent l’eau. Comme mère, comme membre d’un clan, comme membre des Premières Nations et comme professeure, l’auteure se sent responsable du partage de ses connaissances. Cette réflexion est basée sur son travail avec les aînées et les tenants du savoir traditionnel en Ontario, surtout de celui qui se rapporte à l’eau. L’information part de deux projets majeurs dans lesquels elle a été impliquée.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droit; droit de l'environnement; eau; environnement; féminisme autochtone; ontario; point de vue situé; pol4105; premier cycle; pédagogie; périodes historiques; régions géographiques; science politique et droit; sciences de l'éducation; thématiques; transmissions; écoféminisme; écoféminisme amérindien

Firekeepers of the twenty-first century: First Nations women chiefs - Voyageur, Cora Jane (McGill-Queen's University Press, 2008)
A quiet revolution is occurring in Canada's First Nations communities, with changes taking place on social, political, and economic fronts and a significant redistribution of power. Changes to the Indian Act in 1951 paved the way for women to become officially involved in reserve politics, and with governments responding to the demand of First Nations for self-government, positions once held exclusively by men are now being filled by women. Beginning with Elsie Knott, the first female chief in Canada, Cora Voyageur presents the lives of sixty-four of the ninety women chiefs who have assumed the traditionally male role of elected First Nations leadership. Using a range of qualitative research strategies, surveys, participant observation, interviews, and discussions with focus groups, Voyageur presents the colonial histories behind the issues that contemporary Aboriginal communities struggle with and delineates the resulting leadership dilemmas for chiefs, while also articulating a story that is unique to First Nations women. Voyageur asks women chiefs about what inspired them to become leaders, how they've maintained their priorities, and the personal and professional costs and rewards involved in their positions. Firekeepers of the Twenty-First Century is a groundbreaking work that examines the experiences of women as they negotiate multiple roles and navigate the worlds of gender, race, and reserve politics.
Section: xxi, 157 pages
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; entretien; femmes* au pouvoir; femmes* autochtones; féminisme autochtone; féminisme décolonial; gouvernance; histoire et politique; militance; pol4105; pouvoir; premier cycle; premières nations; périodes historiques; régions géographiques; sciences humaines; sociologie; système colonial; systèmes d'oppressions; thématiques